Determinants of workers' remittances: evidence from the European Neighbouring Region - Ioana Schiopu; Nikolaus Siegfried (European Central Bank (ECB), 2006)
Workers' remittances have become the second largest source of net financial flows to developing countries. However, the main motives for sending remittances remain controversial. This paper examines the importance of altruistic versus investment motives using a new panel data set of bilateral flows from 21 Western European to 7 EU neighbouring countries. We find that altruism is important for remitting, as the GDP differential between sending and receiving countries is positively correlated with the average remittance per migrant. By contrast, interest rate differentials are insignificant, suggesting a weak investment motive. Finally, migrants' skills raise remittances, while a large informal economy in the sending country depresses official remittance flows.
Keywords: D13; D64; F22; F24; O15; 330; altruism; balance of payments; migrants' skills; migration; remittances; Rücküberweisungen; Altruismus; Auslandsinvestition; Zahlungsbilanz; EU-Staaten; Osteuropa